Chronic Stress and Negative Marital Quality Among Older Couples: Associations With Waist Circumference. (24th September 2016) - Birditt, Kira S; Newton, Nicky J; Cranford, Jim A; Webster, Noah J
Abstract: Objective: More than a third of the U.S. population of older adults is obese. The present study tests the Dyadic Biopsychosocial Model of Marriage and Health, which hypothesizes that, among married couples, individual and partner chronic stress predicts increased waist circumference and these links are exacerbated in negative quality marriages. Method: Participants were from the nationally representative longitudinal Health and Retirement Study (HRS). A total of 2, 042 married individuals (in 1, 098 married couples) completed psychosocial and waist circumference assessments in 2006 and 2010. Analyses examined whether negative marital quality and chronic stress in Wave 1 (2006) were associated with changes in waist circumference over time. Results: Actor–partner interdependence models revealed that greater partner stress, rather than individuals' own reports of stress, was associated with increased waist circumference over time. Higher perceived negative marital quality among husbands and lower negative marital quality among wives exacerbated the positive link between partner stress and waist circumference. Discussion: Consistent with the Dyadic Biopsychosocial Model of Marriage and Health, partner stress has direct associations with waist circumference among couples and this link is moderated by negative marital quality. Thus, dyadic perceptions of stress and negative marital quality are important to consider for understanding marriage and obesity.